Analisis Manajemen Asset Dan Penjualan Terhadap Tingkat Pengembalian Aktiva - Rismawan, Risky; ., Iswandi (Jurnal Ilmiah Manajemen Kesatuan, 2017)
To be able to grow and thrive in running operations, companies require assets and substantial sales. Therefore, companies are faced with the problem of how to manage these assets and generate sales. Effective management and efficient assets will generate large sales, which will affect the rate of return on assets of the company. The purpose of this study is to determine how much asset management, sales and return on assets produced by PT. Indofood Sukses Makmur Tbk and PT. Mayora Indah Tbk, as well as asset management and sales effect on the return of assets at PT. Indofood Sukses Makmur Tbk and PT. Mayora Indah Tbk, with the period of 2005 through 2014. The results showed that PT. Mayora Indah Tbk. produced the highest and more stable Total Assets Turnover (TATO). The same amount of assets that can increase the sales volume of its assets when turnover increased or enlarged. PT. Mayora Indah Tbk also has a fairly steady increase in sales from year to year compared to PT. Indofood Sukses Makmur Tbk. Additionally Return on Assets (ROA) is best produced by PT. Mayora Indah Tbk which in 2009 amounted to 11.5%, a positive ROA shows that from the total assets used to operate, PT Mayora Indah Tbk. able to generate profits. The higher of ROA, the better, because this ratio indicates that the company performs its operations effectively and resulting in notable returns. The simultaneous test shows that the asset management and sales on the return of assets have no significant effect